Investigating Non-Native English Teachers’ Strategies in Teaching English Speaking to Young Language Learners: A Case Study - Fadhilah, Mega; Nuraeni, Nuraeni (Linguists : Journal of Linguistics and Language Teaching, 2019)
Teaching English speaking to young language learners requires particular treatments. For non-native English teachers, certain problems might be the difference of both students‟ and teachers‟ language and cultural shock. The aims of this study were to investigate non-native English teacher‟s strategies in teaching speaking to young learners, to find the barriers faced by the teacher and also how they overcome the barriers. Qualitative method was employed to conduct this study. Two non-native English teachers who taught in elementary level in Southern Thailand were the participants of this study. The data and information needed were collected through twenty five questions in a questionnaire sheets and several questions related with the topic were asked in an interview session. The result of this study revealed that the respondents used several strategies while teaching speaking in elementary level, such as applying Audio Lingual Method and Communicative Language Teaching method, playing games, doing group-work and drilling activities to enrich the students‟ speaking ability. Besides, the non-native English teachers also implemented intrinsic method in order to make students interested in learning, such as keep motivating students about the importance of learning English, giving reward as an appreciation of what they reached and creating a stress-free environment in the classroom. The non-native English teachers also agreed that they needed a lot of patience in facing the young learners‟ behavior during the English teaching learning process.